The Moderating Role of Profitability: Good Corporate Governance and Company Size on Financial Distress - Phania, Fraciska; Maran (Jurnal Bisnis dan Manajemen, 2025)
The phenomenon of financial distress is increasingly drawing attention due to its capacity to serve as an early warning sign of potential corporate failure. This research investigates the moderating role of profitability in the association between good corporate governance (GCG) and company size and the chances of encountering financial distress, focuses on healthcare entities traded on the Indonesia Stock Exchange from 2020 until 2024. A quantitative methodology was adopted, utilizing Moderated Regression Analysis and panel data regression, using data analyzed through EViews 12 software. This research involved 21 purposively selected firms, resulting in 105 firm-year observations. Financial distress levels were calculated using the Altman Z-Score model. The findings reveal that while GCG and company size jointly influence financial distress, their individual influences are statistically insignificant. Profitability plays a significant moderator in the correlation between GCG and financial distress, but not between company size and financial distress. This study provides actionable insights for corporate decision makers and regulators, particularly in developing governance frameworks and profitability-based strategies to mitigate financial vulnerability. Moreover, it offers contextually grounded implications for strengthening financial sustainability within Indonesia’s healthcare sector an industry where stability and ethical stewardship are vital to maintaining public trust.